Violence and post-conflict transitions: Twin challenge for the EU in the "Arab Spring" - Marco Overhaus (Stiftung Wissenschaft und Politik (SWP), 2011)
In several countries of the Middle East and North African region, the "Arab Spring" has given rise to violent contests for power. The European Union is ill-suited to effectively deal with these kinds of crises. By contrast, compared to bilateral actors such as former colonial powers or the United States, the EU has a potential strength when it comes to supporting post-conflict transitions in a way that is less likely to be rejected by domestic actors as illegitimate interference. Because violent crises and post-conflict transitions are strongly interlinked challenges, the European Union needs to deal with its deficits and build on its strengths simultaneously in both conflict phases
Keywords: 320